The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/17531934211050559
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and recommendations for revision of thumb carpometacarpal resection arthroplasty

Abstract: This study investigated revision surgery for the thumb after failed trapeziectomy with ligament reconstruction and tendon interposition and defined a revision concept. Twenty-four patients with 25 affected thumbs were examined at a mean of 5.5 years after their last revision operation. Pain during daily activities was 2.7 on a 0–10 numeric rating scale, pain at rest was 1.6 and the brief Michigan Hand Outcomes Questionnaire score was 63. Although 68% of patients indicated that their thumb was better than befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 29 publications
(49 reference statements)
0
19
0
10
Order By: Relevance
“…For the management of this potential burden of disease, trapeziectomy with or without reconstruction is a relatively simple, economical and successful operation. Unfortunately, while most patients benefit from a trapeziectomy, a failed trapeziectomy is a difficult problem to manage (Herren et al., 2021). Chatgroups among surgeons are replete with pleas for advice from colleagues for difficult revision cases, with options ranging from tendon reconstruction (if not performed at the primary surgery), silastic implant, suspension with synthetic ligaments, insertion of allograft or of gelatine sponge, index to thumb metacarpal arthrodesis and scaphometacarpal arthroplasty with a reverse silicon metacarpophalangeal (MCP) arthroplasty or a Maïa prosthesis (Chiche et al., 2020; Herren et al., 2021; Hess et al., 2018; Johnson and Chung, 2022; Taleghani et al., 2022; Umarji et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the management of this potential burden of disease, trapeziectomy with or without reconstruction is a relatively simple, economical and successful operation. Unfortunately, while most patients benefit from a trapeziectomy, a failed trapeziectomy is a difficult problem to manage (Herren et al., 2021). Chatgroups among surgeons are replete with pleas for advice from colleagues for difficult revision cases, with options ranging from tendon reconstruction (if not performed at the primary surgery), silastic implant, suspension with synthetic ligaments, insertion of allograft or of gelatine sponge, index to thumb metacarpal arthrodesis and scaphometacarpal arthroplasty with a reverse silicon metacarpophalangeal (MCP) arthroplasty or a Maïa prosthesis (Chiche et al., 2020; Herren et al., 2021; Hess et al., 2018; Johnson and Chung, 2022; Taleghani et al., 2022; Umarji et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, while most patients benefit from a trapeziectomy, a failed trapeziectomy is a difficult problem to manage (Herren et al., 2021). Chatgroups among surgeons are replete with pleas for advice from colleagues for difficult revision cases, with options ranging from tendon reconstruction (if not performed at the primary surgery), silastic implant, suspension with synthetic ligaments, insertion of allograft or of gelatine sponge, index to thumb metacarpal arthrodesis and scaphometacarpal arthroplasty with a reverse silicon metacarpophalangeal (MCP) arthroplasty or a Maïa prosthesis (Chiche et al., 2020; Herren et al., 2021; Hess et al., 2018; Johnson and Chung, 2022; Taleghani et al., 2022; Umarji et al., 2012). However, the withdrawal from the market of the Swanson trapezial implant and the Tie-in trapezium implant, together with a number of pyrocarbon implants, mean that some of these options are no longer available.…”
Section: Introductionmentioning
confidence: 99%
“…A recent good example, also published in the Journal of Hand Surgery European , is a series of 24 patients with 25 thumbs who underwent revision due to persistent symptoms after trapeziectomy (Herren et al., 2021). For revision cases, they recommended that a tendon procedure should be performed in cases where the primary operation was a simple trapeziectomy or a new supplementary tendon procedure, if this was used the first time.…”
mentioning
confidence: 99%
“…Although 68% of patients indicated that their thumb was better than before the primary surgery, the outcome after revision surgery was less favourable than that reported for primary trapeziectomy with ligament reconstruction and tendon interposition. Herren et al., (2021) also presented an algorithm that was necessarily complex to take into account the several reasons for ongoing symptoms. In my opinion, revision of failed trapeziectomy remains a very challenging situation and without any guarantee for success, which emphasized again the need to counsel patients preoperatively.…”
mentioning
confidence: 99%
“…We now know the condition is extremely common, still more common in women than men, and that injury constitutes only a very small percentage of cases. Interestingly, the incidence of patients with ‘ inferior’ results postoperatively or those who said they were ‘ not glad to have had the operation’ (as Gervis put it) remains small, the same today as it was 70 years ago (Herren et al., 2021).…”
mentioning
confidence: 99%